Geomorphological reconnaissance of the Psathopyrgos and Rion-Patras Fault zones (Achaia, NW Peloponnesus). - Palyvos, N.; Pantosti, D.; Stamatopoulos, L.; De Martini, P. M. (Bulletin of the Geological Society of Greece, 2007)
In this communication we discuss reconnaissance geomorphological observations along the active Psathopyrgos and Rion-Patras (NE part) fault zones. These fault zones correspond to more or less complex rangefronts, the geomorphic characteristics of which provide hints on the details of the fault zone geometries, adding to the existing geological data in the bibliography. Aiming at the identification of locations suitable or potentially suitable for geomorphological and geological studies for the determination of fault slip rates in the Holocene, we describe cases of faulted Holocene landforms and associated surficial deposits. We also discuss problems involved in finding locations suitable for geological (paleoseismological) studies for the determination of the timing of recent earthquake ruptures, problems due to both man-made and natural causes.